Studi Kasus: Penerapan Terapi Bermain Cotton Ball Hockey pada Anak Usia Sekolah dengan Bronkopneumonia di RSIJ Sukapura - Khairunnisa Khairunnisa; Amanda Gita Dwi Hapsari; Arsyta Tiara Putri; Awaliah Awaliah (Lembaga Pengembangan Kinerja Dosen, 2026)
Bronchopneumonia often causes respiratory distres in school-age children. Non-pharmacological, play-based interventions, such as cotton ball hockey, can be a child-friendly alternative to improve respiratory function. To evaluate the implementation of cotton ball hockey play therapy in improving respiratory status among school-age children with bronchopneumonia at Sukapura Islamic Hospital. A case study of two school-age children with bronchopneumonia. The cotton ball hockey play therapy intervention was conducted for 3 days, twice daily for 10-15 minutes. Evaluation included measuring respiratory rate, oxygen saturation, and clinical observations before and after therapy. Cotton ball hockey play therapy can improve respiratory status and increase oxygen saturation in children. Cotton ball hockey play therapy is a non-pharmacological nursing intervention that can improve respiratory status in school-age children with bronchopneumonia. This intervention is recommended for implementation in pediatric nursing practice.